Ahmed Ibn Fadlan and Bayard Taylor: Travel Writers or Translators? - Elbarbary, Ayman S. (Vertimo studijos, 2023)
In this article, two works of travel writing, Resala (922) by Ahmed Ibn Fadlan and Travels in Arabia (1889) by Bayard Taylor, are explored to show how the genre as a whole serves as one way of translating culture in order to better understand and discover it. It examines how ideology affects cultural translation in travel writing and how this leads to othering. We begin with close readings of the texts for major content themes, including religion, sex, traditions, etc. These are analyzed for instantiations of inaccurate cultural translation, ideology, and othering. The use of pronouns, nouns, and adjectives is looked at to explore their othering effect. The results show that inaccurate cultural translations are sometimes influenced by ideology and usually lead to othering. The analyzed samples of travel writing rather reveal the predominant mindsets and leanings of their authors and cultures of their origin than those they attempt to introduce to their readers.
Keywords: cultural translation; travel writing; othering; ideology; Eastern Europe; Middle East